Integrated remediation through solidification and dewatering of contaminated soil from laboratory investigation to in-situ application - Tingting Deng; Yongfeng Deng; Hang Liu; Fang Liu; Zhenshun Hong; Xueyu Geng (Soils and Foundations, 2025)
Solidification/stabilization of heavy metal contaminated soils often falls short of achieving the desired quality due to challenges in effectively controlling mixing uniformity. Optimization of mixing equipment and construction technology is a common way to improve mixing uniformity. However, optimizing mixing equipment has high cost, limited site applicability and limited effect on improving uniformity. To solve the problem, a combined solidification/stabilization - vacuum dewatering technique (SSVD) was proposed, which is to increase the water to binder ratio to make the binder and heavy metal contaminated soils mixed evenly and then immediately vacuum dewatering. Its efficiency was explored through both laboratory experiments and a pilot project. Because zinc is a well-known factor that decreases compressive strength and cementation speed, zinc contaminated soil was studied. The findings indicate that the vacuum dewatering successfully removes water from solidified soils during the initial 12 h of setting and hardening in the field, indicating the feasibility of more water incorporation to raise the mixing workability. Furthermore, it can enhance the microstructure to prevent the migration of pollutant, and extract the heavy metals from the solidified mass by the cation exchanges. After 28 days of curing, laboratory tests showed a 1.9-4.1 times’ increment in strength and a 1.7-17.8 times’ reduction in permeability after dewatering. In the field, these values increase by 1.8 times and decrease by 1.7 times, respectively. The Zn2+ observed diffusivity also decreases by 2.0 times after dewatering in the laboratory. Microstructure analysis reveals that the vacuum dewatering significantly reduces the porosity of the solidified matrix, thereby enhancing its integrity. The proposed technology holds potential for the application not only in the solidification/stabilization remediation but also in the soft ground improvement in term of the better workability and homogeneity, stronger densification and capsulation, and less pollutant retention and binder consumption.